2022
DOI: 10.3847/psj/ac0f82
|View full text |Cite
|
Sign up to set email alerts
|

The Lunar Geophysical Network Landing Sites Science Rationale

Abstract: The Lunar Geophysical Network (LGN) mission is proposed to land on the Moon in 2030 and deploy packages at four locations to enable geophysical measurements for 6–10 yr. Returning to the lunar surface with a long-lived geophysical network is a key next step to advance lunar and planetary science. LGN will greatly expand our primarily Apollo-based knowledge of the deep lunar interior by identifying and characterizing mantle melt layers, as well as core size and state. To meet the mission objectives, the instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…Furthermore, our results highlight and strengthen the case for a still tectonically active Moon within and outside of the Maria basins. To further uncover the active lunar tectonism, the future installation of a geophysical network on the Moon is highly desirable (Fuqua Haviland et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results highlight and strengthen the case for a still tectonically active Moon within and outside of the Maria basins. To further uncover the active lunar tectonism, the future installation of a geophysical network on the Moon is highly desirable (Fuqua Haviland et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A better site for this science objective would be the far side Korolev crater residing by the equator, about 23° from the antipodes (by which we understand the center of the farside). It is now considered as one of the possible landing sites for the Lunar Geophysical Network (LGN) mission proposed to arrive on the Moon in 2030 and to deploy packages at four locations to enable geophysical measurements for 6–10 years (Fuqua Haviland et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Oberst (1987) suggested that lunar scattering and internal attenuation are factors that bias the spectral shape of corner frequency estimates, an effect that could potentially explain the discrepancy between fault scarpbased estimates here and waveform propagation estimates of stress drop. Future recordings by new seismometers deployed on the Moon by the Farside Seismic Suite (Panning et al 2022), Artemis astronauts, or a Lunar Geophysical Network (Haviland et al 2021) will be essential for understanding the faulting mechanism in more detail.…”
Section: Seismicitymentioning
confidence: 99%